NCOG-03. COGNITIVE CONCERNS AND PERFORMANCE IN PATIENTS WITH METASTATIC NON-SMALL CELL LUNG CANCER (mNSCLC). (11th November 2019) - Eggen, Annemarie; Richard, Nadine; Shen, Gerald; Shultz, David; Leighl, Natasha; Liu, Geoffrey; Sun, Alexander; Bosma, Ingeborg; Reyners, Anna; Jalving, Mathilde; Rodin, Gary; Edelstein, Kim
Abstract: INTRODUCTION: Cognitive concerns and objective cognitive impairment are both common in cancer patients, although the relationship between these variables is uncertain. Brain metastases have the potential to affect both outcomes. We examined the relationships between cognitive concerns, cognitive performance, and psychological disturbance in mNSCLC patients with and without brain metastases. METHODS: mNSCLC patients completed standardized neuropsychological tests (HVLT-R, TMTA/B, COWA) and questionnaires measuring cognitive and neurobehavioral concerns, depression, demoralization, self-esteem, illness intrusiveness, and physical symptoms. Perceived cognitive impairment was defined as FACT-Cog scores ≤1.5 SD below the normative mean. Impaired cognitive performance was defined as ≥2 test scores ≤1.5 SD or one test score ≤2.0 SD below normative means. Multivariate analyses used the mean composite of neuropsychological test z-scores (COG-comp). Progressive disease (extra- and/or intracranial) was defined as radiological progression or clinical deterioration within one month before the study. RESULTS: 74 patients participated (53% female; median age 62 (37–82); 30% EGFR mutated). Time since mNSCLC diagnosis was 11 months (median; 0–89). 50% had brain metastases, 21 of whom received cranial radiation (11 SRS, 10 WBRT±SRS). 27% reported cognitive concerns and 42% were impaired on objective testing (HVLT-R:34%, TMT:27%, COWA:16%). Neither was more common in patients with brain metastases. COG-comp (mean±SD: –0.39±0.91) was unrelated to cognitive concerns. In multivariate analyses, less depression (p< 0.01) and illness intrusiveness (p=0.03), and absence of disease progression (p=0.03) were related to better perceived cognitive function. No significant associations were found between cognitive performance and demographic, disease, or psychological variables. CONCLUSION: Cognitive impairment is common in mNSCLC patients with or without brain metastases, but is independent of cognitive concerns. Cognitive concerns which are linked to depression, illness intrusiveness and disease progression, may be more likely to reflect the impact of cognitive changes in daily life. Both merit further clinical and research attention.